1993
DOI: 10.1177/104063879300500111
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Characterization of a Pleomorphic Gram-Negative Rod Associated with Avian Respiratory Disease

Abstract: Abstract. An unidentified, pleomorphic, gram-negative rod (PGNR) bacterium has been isolated from domestic fowl with respiratory disease. The PGNR was isolated in 5% of turkey accessions and 3% of chicken accessions, primarily from the respiratory tract. Preliminary characterization of this organism included reviewing accession records, conducting cultural and biochemical tests, and analyzing cellular fatty acids. The PGNR was also compared with other bacteria capable of inhabiting the avian respiratory system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
50
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 2 publications
1
50
0
Order By: Relevance
“…It was further characterized by Charlton et al (1993) as Pasteurella-like or Kingella-like, and the name Ornithobacterium rhinotracheale was proposed by Vandamme et al (1994). Retrospective studies revealed that ORT had been isolated as early as 1981 and since then it has emerged as an important pathogen of poultry worldwide (Pagés et al, 1995;van Empel & Hafez, 1999;Chin et al, 2003;Bisschop, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was further characterized by Charlton et al (1993) as Pasteurella-like or Kingella-like, and the name Ornithobacterium rhinotracheale was proposed by Vandamme et al (1994). Retrospective studies revealed that ORT had been isolated as early as 1981 and since then it has emerged as an important pathogen of poultry worldwide (Pagés et al, 1995;van Empel & Hafez, 1999;Chin et al, 2003;Bisschop, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported mostly in chickens and turkeys and less frequently, in other species such as duck, goose, pheasant, partridge, quail, guinea fowl, ostrich, pigeon, gull and rook (Charlton et al, 1993;van Empel & Hafez, 1999;Ley et al, 2000;Chin et al, 2003;Bisschop, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical symptoms associated with O. rhinotracheale infection have included lacrimation, nasal exudates, sinusitis, dyspnoea, coughing, oedema in facial subcutis, growth retardation and a drop in feed consumption (Charlton et al, 1993;DeRosa et al, 1996;Back et al 1998;Canal et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Majority of cultured bacteria found in the lungs and trachea of birds belonged to phyla Proteobacteria, Firmicutes, Tenericutes, Actinobacteria, Bacteroidetes and Chlamydia/Verrucomicrobia (Murthy et al 2008, Charlton et al 1993, Byrum & Slemons 1995. Additionally, culture independent analyses detected groups of fastidious or poorly represented taxons belonging to Fusobacteria, Acidobacteria, Chloroflexi, Cyanobacteria and Deinococcus -Thermus in the lower respiratory tract of poultry.…”
mentioning
confidence: 99%